Digital Citizenship Education in Islamic Religious Education: Cultivating Responsible Muslim Citizens in the Digital Society - Faruk Kerem Sentürk; Ihsan Yilmaz; Esraa Al-Sarray; Ainul Jaria Maidin (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2025)
Digital citizenship has become a fundamental competency for students navigating increasingly complex digital environments. Nevertheless, its integration into Islamic Religious Education remains underexplored. This study aims to develop a conceptual model for integrating digital citizenship education with Islamic ethical principles to foster responsible digital behavior among Muslim students. A mixed-method design was employed involving surveys of 436 students, interviews with teachers, and focus group discussions with educational experts. Quantitative data were analyzed using Structural Equation Modeling, while qualitative findings were examined through thematic analysis. The results reveal that digital citizenship education integrated with Islamic values significantly enhances students’ digital responsibility, media literacy, online ethics, cyber safety awareness, and respectful digital communication. Students also demonstrate greater critical evaluation of online religious content and increased resistance to misinformation and hate speech. The novelty of this research lies in proposing the Islamic Digital Citizenship Education Model, integrating digital competence, Qur'anic ethics, civic responsibility, and media literacy into a unified framework for Islamic Religious Education